The 3rd Canadian Symposium on Hepatitis C Virus: Expanding Care in the Interferon-Free Era. Issue 9 (2014) - MacParland, Sonya A; Bilodeau, Marc; Grebely, Jason; Bruneau, Julie; Cooper, Curtis; Klein, Marina; Sagan, Selena M; Choucha, Norma; Balfour, Louise; Bialystok, Frank; Krajden, Mel; Raven, Jennifer; et al.
Abstract : Hepatitis C virus (HCV) currently infects approximately 250, 000 individuals in Canada and causes more years of life lost than any other infectious disease in the country. In August 2011, new therapies were approved by Health Canada that have achieved higher response rates among those treated, but are poorly tolerated. By 2014/2015, short-course, well-tolerated treatments with cure rates >95% will be available. However, treatment uptake is poor due to structural, financial, geographical, cultural and social barriers. As such, 'Barriers to access to HCV care in Canada' is a crucial topic that must be addressed to decrease HCV disease burden and potentially eliminate HCV in Canada. Understanding how to better care for HCV-infected individuals requires integration across multiple disciplines including researchers, clinical services and policy makers to address the major populations affected by HCV including people who inject drugs, baby boomers, immigrants and Aboriginal and/or First Nations people. In 2012, the National CIHR Research Training Program in Hepatitis C organized the 1st Canadian Symposium on Hepatitis C Virus (CSHCV) in Montreal, Quebec. The 2nd CSHCV was held in 2013 in Victoria, British Columbia. Both symposia were highly successful, attracting leading international faculty with excellent attendance leading to dialogue and knowledge translation among attendees of diverse backgrounds. The current article summarizes the 3rd CSHCV, held February 2014, in Toronto, Ontario.